Моделювання коливального руху віброплощадки для ущільнення бетонної суміші з лінійним магнітоелектричним двигуном - Бєлікова, Ю.О.; Бондар, Р.П.; Голенков, Г.М.; Подольцев, О.Д. (Електротехніка і електромеханіка, 2011)
A Simulink model of a two-mass system of a linear permanent magnet motor – a platform-type vibrator is developed. Resonant characteristics of this system and efficiency of energy conversion are studied